Alternative fuel from agricultural wastes - Najdenov, O. (ТДАТУ, 2018)
Agriculture is the largest contributor of any resource sector of the country. It is also a large generator of waste materials. Agricultural waste recycling is a growing business, as more and more farms and companies turn to alternate ways to process waste products instead of sending them to landfill. Production of alternative fuel from agricultural wastes is a new perspective direction for investing. This happens because of rising prices for hydrocarbon fuels and the exhaustion of its world reserves.
Keywords: аgriculture; waste materials; growing business; rising prices